AB0549 Can the overall thrombotic risk in systemic lupus erythematosus be determined? the combined role of classic cardiovascular factors and antiphospholipid antibodies. (12th June 2018) - Â.Mota, S.; Cunha, I.; Andrade, J.; Eira, C.; Machado, S.; Tavares, J.; Romão, V.; Silvério, R.; Martins, C.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disorder. Antiphospholipid syndrome (APS) is a thrombotic disorder associated with the presence of antiphospholipid antibodies (APA) and increased cardiovascular risk (CVR). Framingham (FRM) and SCORE (Systematic Coronary Risk Evaluation) scales are available CVR assessment systems. aGAPSS (adjusted Global AntiphosPholipid Syndrome Score) combine positive APA and CVR factors, which was suggested to determine the thrombotic risk in persistently positive APA (PPAPA) patients. Objectives: To determine the role of the thrombotic factors in SLE patients, considering CVR factors and APA. To access the application of different thrombotic risk scales. Methods: A retrospective cohort study of 84 patients with SLE followed in an outpatient setting of a Portuguese central hospital was performed. The study evaluated patient gender, current age, age at diagnosis, duration of illness, presence of another autoimmune disease (AID), CVR factors [obesity (OB), diabetes (DB), arterial hypertension (AH), dyslipidaemia (DL), smoking (SM)], presence of APA, treatment, dose and duration of steroids. The FRM, SCORE and aGAPSS scores were calculated. The data was analysed using SPSS and considered significant if p<0.05. Results: Table 1 characterises the study population. Male patients had a higher prevalence of AH (p=0.022), DL (p=0.047), and SM (p=0.001), with a risk of 11%–20% in the FRM scale and a risk of 5%–14% in the SCORE (p=0.000). Female patients had a higher presence of another AID (p=0.014) and treatment with disease-modifying antirheumatic drugs (p=0.014). FRM scale reveals a risk of 11%–20% in the presence of AH and >20% in SM (p=0.001). The SCORE scale reveals a risk of 5%–9% in the presence of AH (p=0.003) and 10%–14% in DL (p=0.024). When the risk is 6%–20% in the FRM scale, the risk is lower in SCORE (p=0.000). APA does not correlate with an increased CVR. All APA are associated with another AID, APS and PPAPA. The aGAPSS associates a score of 7–12 if another AID is present (p=0.000); 4–9 with APS;>7 with PPAPA (p=0.000); 4–6 with DB (p=0.039), DL (p=0.002) and AH (p=0.000);>7 with lupus anticoagulant (LA), >7 with anticardiolipin antibodies (aCL) and >12 with anti-β−2glycoprotein-I antibody (antiβ2GPI) (p=0.000). Conclusions: This study highlights the existence of thrombotic factors in SLE. Their risk is even more elevated when another AID is present. The FRM and SCORE scales reflects the CVR. In SLE patients both the CVR factors and the presence of APA must be evaluated. Therefore, not only should the FRM scale be calculated, but also the global thrombotic risk, using the aGAPSS, must be accessed. References: [1] Sarzi-Puttini P, Atzeni F, Carrabba M. Cardiovascular risk factors in systemic lupus erythematosus and in antiphosphlipid syndrome. Minerva Med2003;94(2):63–70. [2] Sciascia S, Radin M, Sanna G, Cecchi I, Roccatello D, Bertolaccini ML. Clinical utility of the global anti-phospholipid syndrome score for risk stratification: a pooled analysis. Rheumatology2018. Disclosure of Interest: None declared